2008
DOI: 10.1597/07-129.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Grading of Pierre Robin Sequence

Abstract: Since implementation, this new classification of babies with PRS into three grades has clarified care pathways and enhanced communication between the Cleft Clinical Nurse Specialists and other health professionals involved with the care of these babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 7 publications
0
43
0
3
Order By: Relevance
“…A possibility for the lack of correlation between mandible size and airway obstruction is the presence of additional lower airway anomalies, a common finding in prior studies. 32,33 Classification systems based on airway obstruction and feeding difficulties 34 are helpful but are not statistically associated with any outcome measures. Furthermore, feeding difficulties can be related to obstructive breathing patterns or to an underlying syndrome or disease state outside the tongue base and jaw.…”
Section: Discussionmentioning
confidence: 99%
“…A possibility for the lack of correlation between mandible size and airway obstruction is the presence of additional lower airway anomalies, a common finding in prior studies. 32,33 Classification systems based on airway obstruction and feeding difficulties 34 are helpful but are not statistically associated with any outcome measures. Furthermore, feeding difficulties can be related to obstructive breathing patterns or to an underlying syndrome or disease state outside the tongue base and jaw.…”
Section: Discussionmentioning
confidence: 99%
“…6,62,100 Cole et al 101 suggested a unique classification system for RS based on functional parameters: severity of airway obstruction, breathing, and feeding difficulties. Care and caution must be exercised when interpreting recommendations for the whole group, because morphologic phenotype, airway physiology, and severity of RS vary.…”
Section: Conclusion and Offeringmentioning
confidence: 99%
“…A wide range of clinical manifestations exists, but the main clinical problems faced by clinicians include upper airway obstruction and feeding difficulties [7]. …”
Section: Introductionmentioning
confidence: 99%